Rancang Bangun Game Edukasi Keamanan Berkendara Berbasis Mobile - Fitriani, Leni; Wafa, Adhima Rasyadani (Jurnal Algoritma, 2025)
Driving safety is an important aspect in reducing the risk of traffic accidents. This research aims to develop a mobile-based educational game as a learning media about driving safety. The methodology used is Digital Game-Based Learning (DGBL) - Instructional Design (ID) with stages of Analysis, Design, Development, Quality Assurance, and Implementation & Evaluation. Testing is done with Black-box Testing and effectiveness evaluation using Likert scale. The results showed that this educational game scored 94.44% in the strongly agree category, indicating high effectiveness in improving users' understanding of driving safety. The contribution of this research is to offer an interactive learning approach that can be applied in driving safety education more broadly, with the potential to expand to other platforms to increase user reach.